Sugar and Spice, and Everything Nice: Exploring Prosocial Development Through Infancy and Early Childhood - Markus Paulus (Frontiers Research Topics, 2015)
Prosocial behaviors such as sharing, helping, and comforting begin to emerge early in development. The presence of these prosocial behaviors is important not only in childhood, but throughout one's lifetime, as behaving prosocially is important for social functioning and maintaining social relationships. For many years researchers have been interested in how and when these behaviors develop, as well as how these behaviors are influenced by a variety of factors. Recently however, exciting new research has shown novel and surprising findings, particularly on the early development and ontogenetic origins of prosocial behavior. Research is this area is important, as by understanding what influences prosocial behavior, we may be better able to sustain and support the development of prosociality. Further, a richer understanding may help us to be better able to mediate factors that impede or negatively influence positive social behaviors, as well as negate triggers that may lead to negative social behaviors. Many theoretical views guide different streams of developmental research in this field. Here, we will bring together scholars from various theoretical backgrounds, to collectively explore the development of early prosocial behaviors from early infancy to early school aged children. Contributors will offer insights using a variety of methodologies, from various resource allocation paradigms derived from economist game theorists, to looking time paradigms and more. Together we seek to broadly explore questions pertaining to prosocial development, for example- at what age do prosocial behaviors, moral understanding, or social selectivity emerge? Contributors will individually address unique research questions across a spectrum of topics. For example, how prosocial behaviors are influenced by underlying mechanisms, such as moral emotions (e.g. guilt and sympathy), will be explored, as will how children's expectations may shape their behaviors, and how they come to care about others. Questions surrounding different contexts will also be investigated. For example, how does empathy influence prosociality? Do children treat partners differently depending on their past behaviors, wealth, or other characteristics? Does whether there is a cost associated with behaving prosocially influence decision-making? By incorporating the work of numerous researchers in the field of prosocial development, who contribute comprehensive reviews of past research, unique theoretical perspectives and empirical approaches, the proposed research topic endeavors to provide new insights into a breadth of prosocial behaviors. In sum, the proposed research topic will contribute to our understanding of prosocial development in the early years by highlighting the relevant factors and contexts under which prosocial behavior emerges.